Systematic Design and Circuit Analysis of Lightning Impulse Voltage Generation on Low-Inductance Loads - Peerawut Yutthagowith; Phattarin Kitcharoen; A. Kunakorn (Energies, 2021)
The well-known circuit for the generation of lightning impulse voltage (LIV) on low-inductance loads was introduced by Glaninger in 1975, and the circuit component selection was proposed by Feser. However, the circuit and the approach for the component selection have some difficulties for which further adjustment is required for obtaining the waveform parameters according to the standard requirement. In this paper, an extended Glaninger’s circuit with an additional series resistor is proposed. Furthermore, a systematic design and circuit analysis of LIV generation for low-inductance loads are developed. With the help of a circuit simulator, the circuit analysis for the component selection is described. The validity of the proposed circuit was confirmed by some experimental results in comparison with the simulated ones. The proposed circuit and component selection provide not only the generation waveform according to the standard requirement but also other promising performances in terms of the wide inductance load range from 400 μH to 4 mH, a voltage efficiency of over 80%, an overshoot voltage of below 5%, an undershoot voltage of below 40%, and a maximum charging capacitance of 10 μF. From the simulated and experimental results, the proposed circuit and component selection approach is very useful for the LIV tests on low-inductance loads instead of using the conventional approach based on trial and error.
Keywords: Lightning and Electromagnetic Phenomena; Electrical Fault Detection and Protection; High voltage insulation and dielectric phenomena